Defect-driven extreme magnetoresistance in an I-Mn-V semiconductor - Yang, Junjie; Wegner, Aaron; Brown, Craig M.; Louca, Despina (Applied physics letters, 2018)
The search for appropriate materials for technological applications is challenging, as real materials are subject to uncontrolled doping and thermal effects. Tetragonal NaMnBi of the I-Mn-V class of antiferromagnetic semiconductors with a Néel transition (TN), above room temperature, can exhibit an extreme magnetoresistance (MR), greater than 10 000% at 2 K and 600% at room temperature and 9 T by quenching disorder into the system. Coupled with the large MR is a re-orientation of the magnetic moment, from a collinear spin arrangement along c to a canted one along the (011) crystallographic axis. The extreme MR is observed in samples with about 15% of Bi vacancies which in turn effectively introduces charge carriers into the lattice, leading to a drastic change in the electronic transport, from semiconducting to metallic, and to the very large MR under the magnetic field. In the absence of Bi defects, the MR is severely suppressed, suggesting that the hybridization of the Mn and Bi orbitals may be key to the field induced large MR. This is the only material of its class that exhibits the extreme MR and may potentially find use in microelectronic devices.